2014
DOI: 10.3109/14992027.2013.876108
|View full text |Cite
|
Sign up to set email alerts
|

Sounds perceived as annoying by hearing-aid users in their daily soundscape

Abstract: Background: The noises in the modern soundscapes continue to increase and are a major

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…Some of the negative effects of disturbing sounds are masking of wanted sounds, stress, sound fatigue and distraction (Sjodin et al, 2012;Canlon et al, 2013). Skagerstrand et al (2014) showed that the majority of people with normal hearing or with hearing impairment who used hearing aids experience disturbing sounds in the daily environment. For hearing aid users, this may reduce hearing aid usage (Kochkin, 2005;McCormack & Fortnum, 2013;Skagerstrand et al, 2014) and thereby reduce the ability to perceive wanted signals.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some of the negative effects of disturbing sounds are masking of wanted sounds, stress, sound fatigue and distraction (Sjodin et al, 2012;Canlon et al, 2013). Skagerstrand et al (2014) showed that the majority of people with normal hearing or with hearing impairment who used hearing aids experience disturbing sounds in the daily environment. For hearing aid users, this may reduce hearing aid usage (Kochkin, 2005;McCormack & Fortnum, 2013;Skagerstrand et al, 2014) and thereby reduce the ability to perceive wanted signals.…”
Section: Introductionmentioning
confidence: 99%
“…Skagerstrand et al (2014) showed that the majority of people with normal hearing or with hearing impairment who used hearing aids experience disturbing sounds in the daily environment. For hearing aid users, this may reduce hearing aid usage (Kochkin, 2005;McCormack & Fortnum, 2013;Skagerstrand et al, 2014) and thereby reduce the ability to perceive wanted signals. Sounds often mentioned as annoying in the study of Skagerstrand et al (2014) were verbal human sounds and sounds from TV/radio, vehicles/machines, and porcelain.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations